Rancangan Pembelajaran Berkarakteristik Inovatif Abad 21 Pada Materi Penguat Audio Dengan Model Pembelajaran Berbasis Proyek (Project Based Learning) di SMKN 1 Adiwerna - Teguh Dwi Puji Santoso (Universitas Pancasakti Tegal, 2022)
This study aims to determine the suitability of the learning design in the 21st century learning model. This research is a document analysis research. The subject of this research is the Learning Implementation Plan (RPP) for audio video engineering teachers on audioamplifier subjects at SMKN 1 Adiwerna. Collecting data using document observation sheets. The results of the analysis show that project-based learning is an ideal learning model to be applied to vocational education, especially in audio reinforcement subjects.